2016
DOI: 10.1136/annrheumdis-2016-eular.4314
|View full text |Cite
|
Sign up to set email alerts
|

FRI0184 Increasing Treatment Time on Infliximab Is Predictive of Incrementally Better Long-Term Retention in Stable Infliximab Rheumatology Patients in Canada:

Abstract: BackgroundA high percentage of patients treated with TNF antagonists discontinue therapy mainly due to lack of efficacy or side effects. Recent studies of stable infliximab (IFX) patients switched to biosimilar infliximab (INB) seem to suggest similar safety and efficacy outcomes as IFX1,2. However, these studies often have small sample sizes, short follow-up periods and, where reported, high discontinuation rates post-switch.ObjectivesTo demonstrate long-term retention patterns of stable Canadian rheumatic di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It is noteworthy that discontinuation rates in historical controls may include not only stable patients who have received the originator for at least 1 year but also patients who have only recently begun treatment [61]. It has been shown that 12-month retention rates increase incrementally with each subsequent year of treatment in patients receiving etanercept or infliximab with rheumatic or psoriatic diseases [72,73], suggesting that patients who have received at least 1 year of biologic therapy are less likely to discontinue treatment than patients initiating therapy. Of the RWE studies reviewed here, the median duration on the originator before the nonmedical switch ranged from 4 to 8 years on originator infliximab and 4 to 6 years on originator etanercept (Table 1).…”
Section: Discontinuation Following a Nonmedical Switchmentioning
confidence: 99%
“…It is noteworthy that discontinuation rates in historical controls may include not only stable patients who have received the originator for at least 1 year but also patients who have only recently begun treatment [61]. It has been shown that 12-month retention rates increase incrementally with each subsequent year of treatment in patients receiving etanercept or infliximab with rheumatic or psoriatic diseases [72,73], suggesting that patients who have received at least 1 year of biologic therapy are less likely to discontinue treatment than patients initiating therapy. Of the RWE studies reviewed here, the median duration on the originator before the nonmedical switch ranged from 4 to 8 years on originator infliximab and 4 to 6 years on originator etanercept (Table 1).…”
Section: Discontinuation Following a Nonmedical Switchmentioning
confidence: 99%